Piezoelectric properties of polymer/lead-free ceramic composites. (2nd August 2016) - Alexandre, M.; Bessaguet, C.; David, C.; Dantras, E.; Lacabanne, C.
ABSTRACT: Thermoplastic/lead-free piezoelectric ceramic composite have been prepared. Sodium niobate (NaNbO3 ) has been chosen for its high Curie temperature. Moreover, it could be synthesized with two different morphologies: NaNbO3 nanowires (NN NW's) and NaNbO3 particles (NN P's). The filler has been dispersed in thermoplastic matrices with different dielectric permittivities ϵ M : PA11 ( ϵ M =   2 ) and polyvinylidene fluoride (PVDF) ( ϵ M =   10 ) . Due to polarization conditions, only ceramic particles are poled. The piezoelectric coefficient (d33 ) has been measured in composites. The higher d33 is recorded in composites based on PA11 (d33 = 6.5 pC.N −1 for 30 vol. % NN NW's). The influence of the NN aspect ratio on PVDF/NN composites has been analysed: the higher d33 (d33 = 2.6 pC.N −1 for 25 vol. %) is recorded in PVDF/NN P's. The major interest of these hybrid lead-free piezoelectric composites is mild poling conditions, ductility and thermal stability of piezoelectric performances.